Synthesis, Characterization, and Dielectric Behaviors of 4-Diethanolaminomethyl Styrene and Benzyl Methacrylate Copolymer and Its Metal Complexes - Acilcses, Aslisah; Oksuz, Fethiye (Hindawi Ltd, 2019)
In this paper, the copolymer of 4-diethanolaminomethyl styrene (DEAMSt) with benzyl methacrylate (BMA) was synthesized and characterized using various spectral techniques such as FT-IR, H-1-NMR, elemental analysis, SEM, XRD, TGA, DTA, and DSC. The copolymer-metal complexes were prepared with Co(II), Ni(II), and Zn(II) metal ions, and poly(DEAMSt-co-BMA) was used as ligand. The copolymer-metal complexes were characterized using elemental analysis. FT-IR, SEM, XRD, magnetic measurements, and the thermal behaviors of the copolymer-metal complexes were studied using TGA, DTA, and DSC. The compositions of DEAMSt and BMA in the copolymer by H-1-NMR spectra were determined as 0.49 and 0.51, respectively. Both poly(DEAMSt-co-BMA) and poly(DEAMSt-co-BMA)-Zn complexes were heated up to various temperatures. As the temperature increased, the intensities of O-H stretching bands at 3125-3429 cm(-1) resulting from hydrogen bond decreased and shifted to high frequency. Gel permeation chromatography was used to determine the average molecular weights and polydispersity index of the poly(DEAMSt0.49-co-BMA) ligand. Both the molecular formula and C, H, and N % were estimated using elemental analysis, and the amounts of metal by mole (%) in the complexes were estimated by SEM-EDX measurements. The XRD patterns of ligand and metal complexes showed that they were of an amorphous nature. The synthesized metal complexes were annealed at 100 degrees C for 1h in order to obtain crystalline metal complexes. After annealing at 100 degrees C, the metal complexes showed the crystalline structure. The SEM and XRD analysis of the metal complexes confirmed that metal ions contributed to the structure of the ligand. According to the magnetic measurements, it was suggested that geometrical structure for all complexes was tetrahedral geometry and the ratio of ligand to metal was found to be 2:1. The dielectric measurements of the ligand and its metal complexes were investigated depend on frequency.